2021
DOI: 10.1590/1981-6723.06820
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and sensory acceptability of beetroot chips pre-treated by osmotic dehydration and ultrasound

Abstract: Red beet (or beetroot) is highly nutritious and can be preserved by drying, in order to avoid wastage, to take advantage of crop surpluses, and to add value during the off-season. The objective of this study was to evaluate the effects of osmotic dehydration (OD) and ultrasound (US) pre-treatments on the nutritional quality and sensory characteristics of dried beetroot chips. The kinetics of moisture loss during OD and US were predicted by fitting the experimental data with thin-layer models. The physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
1
Order By: Relevance
“…treatments without osmotic pre-treatment ( T 1 and T 2) had the highest values compared to osmo-convective treatments at 50 and 60°C but without significant difference ( p > 0.01) between T 2 and T 4. Findings that were different were reported by Peters et al (2021) in beet treated by osmo-convective dehydration at 60°C. The authors reported an increase, mainly in lipid and ash contents.…”
Section: Resultscontrasting
confidence: 89%
“…treatments without osmotic pre-treatment ( T 1 and T 2) had the highest values compared to osmo-convective treatments at 50 and 60°C but without significant difference ( p > 0.01) between T 2 and T 4. Findings that were different were reported by Peters et al (2021) in beet treated by osmo-convective dehydration at 60°C. The authors reported an increase, mainly in lipid and ash contents.…”
Section: Resultscontrasting
confidence: 89%
“…Besides these factors, the pretreatment and combined methods are also effective on the sensory quality of the food products. Osmotic treatment and their combination with ultrasound treatment improved the sensory quality of sweet potato snacks and beetroot chips (Tabtiang et al, 2012; Peters et al, 2021). Increasing ultrasonication time and frequency adversely affected the appearance and texture scores as it caused ruptures and damages in tissue (Roueita et al, 2020; Noshad et al, 2018; Shamaei et al, 2012).…”
Section: Effect Of Advanced Od On Food Productsmentioning
confidence: 99%